Efficacy and safety of cisplatin and paclitaxel (PlaTax regimen) in the neoadjuvant treatment of patients with stage II-III triple-negative breast cancer - O. O. Gordeeva; I. V. Kolyadina; L. G. Zhukova; I. P. Ganshina; G. V. Vyshinskaya; M. A. Kazantseva; M. V. Sukhova; O. E. Ryabishina; E. V. Lubennikova; D. A. Filonenko; E. I. Chichikov; I. N. Polushkina; et al. (ABV-press, 2020)
Background. Treatment results for the patients with stage II-III triple negative breast cancer (TN BC) have to be improved. Not only the new treatment regimens, but new predictive and prognostic factors should to be developed.Materials and methods. We included 98 patients with stage II-III TN BC in our study. We studied efficacy and safety of PlaTax regimen (cisplatin 75 mg / m2 day 1 + paclitaxel 80 mg / m2 days 1, 8, 15, course every 4 weeks) in this cohort of patients. We assessed pathologic response, survival and factors, which were relevant for predicting response and prognose survival.Results. PlaTax regimen is characterized by high efficacy and tolerable toxicity. Clinical efficacy was 85.8 %, pCR achievement was 60.5 %, tpCR achievement was 58.1 %. The regimen has low haematological toxicity (neutropenia III-IV grades - 4.1 %); the most frequent adverse events were polyneuropathy (18.5 %) and decreased renal function (24.5 %). 3-year progression-free survival was 68.4 %, most of the relapses (92 %) occurred during first 2 years. 3 year overall survival was 77.6 %. The most relevant predictive factor was level of Ki-67 ≥50 % (pCR 38.5 % vs. 68.7 %, p = 0.038). pCR achievement was the most important prognostic factor, resulting in improved 3-year progressionfree survival (44.3 % vs. 89.1 %, p <0.0001), and 3-year overall survival (61.5 % vs. 91.6 %, p = 0.001). Not only the residual disease, but also the size of residual tumor was important from prognostic point of view. Other important prognostic factors were size of the tumor, status of regional lymph nodes, grade. Delay in surgical treatment more than a month lead to decreased 3-year progression-free survival: 87.1 % vs. 62.5 % (p = 0.047).Conclusions. Our data suggest that studied regimen could be an option for patients with stage II-III TN BC. The assessment of the predictive and prognostic factors will help improve the treatment results for patients with stage II-III TN BC.